Digital control engineering : analysis and design - Fadali, M. Sami; Visioli, Antonio (Amsterdam : Elsevier Science, 2009)
Digital controllers are part of nearly all modern personal, industrial, and transportation sytems. Every senior or graduate student of electrical, chemical or mechanical engineering should therefore be familiar with the basic theory of digital controllers. This new text covers the fundamental principles and applications of digital control engineering, with emphasis on engineering design.
Chapter 1. Introduction to Digital Control -- Chapter 2. Discrete-Time systems -- Chapter 3. Modeling of Digital Control Systems -- Chapter 4. Stability of Digital Control Systems -- Chapter 5. Analog Control System Design -- Chapter 6. Digital Control System Design -- Chapter 7. State-Space Representation -- Chapter 8. Properties of State-Space Models -- Chapter 9. State Feedback Control -- Chapter 10. Elements of Nonlinear Digital Control Systems -- Chapter 11. Practical Issues -- Appendix I: Table of Laplace and Z-Transforms -- Appendix II: Properties of the Z-Transform -- Appendix III: Review of Linear Algebra.
Includes bibliographical references.
Keywords: DIGITAL CONTROL SYSTEMS